Construction of circRNA-Based ceRNA Network to Reveal the Role of circRNAs in the Progression and Prognosis of Hepatocellular Carcinoma - Deng, Rong; Cui, Xiaohan; Dong, Yuxiang; Tang, Yanqiu; Tao, Xuewen; Wang, Shuyu; Wang, Jincheng; Chen, Lin (Frontiers in Genetics, 2021)
Background: Circular RNAs (circRNAs) are now under discussion as novel promising bio-markers for patients with hepatocellular carcinoma. The purpose of our study is to identify several competing endogenous RNAs (ceRNAs) networks related to the prognosis and progression of hepatocellular carcinoma, to further investigate the mechanism of their influence on tumor progression. Methods: First, we obtained gene expression data related to liver cancer, including miRNA-seq, RNA-seq and clinical information, from the TCGA database. A co-expression network was then constructed through the WGCNA software package in R software, with the purpose of identifying important microRNAs (miRNAs) and messenger RNAs (mRNAs) related to liver cancer. We also applied DAVID (https://david.ncifcrf.gov/summary.jsp) to analyzed the DEmRNAs in the key module, in order to perform functional enrichment analysis including Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene ontology (GO). The data of miRNA expression and clinical information downloaded from TCGA was utilized for survival analysis to detach the prognostic value of the DEmiRNAs of the key module. Results：201 DEmiRNAs and 3783 DEmRNAs were finally identified through differential expression analysis. Further analysis confirmed that 4 miRNAs in the most significant module (blue module), hsa-miR-92b-3p, hsa-miR-122-3p, hsa-miR-139-5p and hsa-miR-7850-5p, were associated with the OS of liver cancer patients. DAVID was used for functional enrichment analysis of 286 co-expressed mRNAs. And metabolic pathways, fatty acid degradation and valine, leucine and isoleucine degradation are the top 3 enriched terms in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Additionally, we compared the miRNA-mRNA interactions prediction results with the differentially expressed and prognostic mRNAs, founding that hsa-miR-92b-3p can be related to cytoplasmic polyadenylation element binding protein 3 (CPEB3) and Acyl-CoA Dehydrogenase Long Chain (ACADL). By overlapping the data of predicted circRNAs utilizing circBank and differentially expressed circRNAs of GSE94508, we screened has_circ_0077210 as the upstream regulatory molecule of hsa-miR-92b-3p. Hsa_circ_0077210/hsa-miR-92b-3p/CPEB3&ACADL were validated in hepatic cell carcinoma (HCC) tissues and human protein atlas (HPA) database. Conclusion: Our research provides a mechanistic elucidation of the unknown ceRNA regulatory network in HCC. Hsa_circ_0077210 might serve as an important biomarker concerning the occurrence and development of HCC.